ANALISIS PERSPEKTIF MAHASISWA DALAM MENYIKAPI ISU SARA MENJELANG PILPRES 2019 - M Khoiruzadid Taqwa; Riki Purwanto; Yoga Putra A; Yonanda Sukma W; Nadia Tresna Raisya; Wahyu Dewi Fatmala; Nur Hidayah; Rosseta Septia Menawati; Khalis Asyifani (UNIVERSITAS SEBELAS MARET (UNS), 2019)
This descriptive qualitative research was conducted in Universitas Sebelas Maret (Sebelas Maret University) (thereafter called UNS) on August-October 2018. The objective of research was to find out type and form of racial, ethnic, and religious issues, UNS students’ perspective and attempt to treat racial, ethnic, and religious issues developing around the Presidential Election of 2019, and the expectation to the implementation of 2019 General Election. The informant of research consisted of students coming from various generations, study programs or departments, and faculties in Universitas Sebelas Maret. Data validation was derived from 2 informants: IA and S as the political observers from FISIP UNS. Data were collected through observation, in-depth interview, and relevant document. Data analysis was conducted using an interactive model of analysis encompassing data collection, data reduction, data display, and conclusion drawing with Gaunt and Ollenburger’s political issue theory. The result of research showed that racial, ethnic, and religious issues developing around the Presidential Election of 2019 involved religious issue, as could be seen in social media and other media. As the agent of change, the students viewed that the public should unnecessarily respond to the unhealthy issues that could result in dissension within society, but they should manifest it into idea and solution. Media should not be partial to one of candidates, and there should be no money politics in Presidential Election of 2019 that could increase the opportunity of corruption. To solve it, socialization and education should be given to society, youth, and students about general election and legislatives should socialize actively about hoax and decline the distribution of unhealthy issue. Keywords: Racial, Ethnic, and Religious Issues, Presidential Election, Student’s Attitude. AbstrakPenelitian deskriptif kualitatif ini dilakukan di Universitas Sebelas Maret pada Agustus-Oktober 2018. Tujuan penelitian ini untuk mengetahui jenis, bentuk isu SARA, perspektif dan upaya mahasiswa UNS dalam menyikapi isu SARA yang berkembang menjelang Pilpres 2019, serta harapannya terhadap pelaksanaan Pemilu 2019. Informan penelitian ini adalah mahasiswa dari berbagai angkatan, program studi dan fakultas di Universitas Sebelas Maret. Adapun untuk validasi data diperoleh dari 2 narasumber, yaitu IA dan S selaku pengamat politik dari FISIP UNS. Data dikumpulkan dengan observasi, wawancara mendalam dan dokumen terkait. Analisis data menggunakan model analisis interaktif yang meliputi pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan dengan teori isu politik dari Gaunt dan Ollenburger. Hasil penelitian menunjukkan bahwa isu SARA yang berkembang menjelang Pilpres 2019 yaitu isu agama, yang diketahui dari media sosial dan media lainnya. Sebagai agen perubahan, mahasiswa berpandangan bahwa seharusnya masyarakat tidak perlu menanggapi isu-isu yang tidak sehat dan dapat membuat perpecahan masyarakat, namun mewujudkannya dalam ide dan solusi. Media hendaknya tidak memihak salah satu calon, serta tidak ada money politic dalam Pilpres 2019 yang dapat menyebabkan peluang korupsi semakin besar. Untuk mengatasi hal tersebut, maka harus dilakukan sosialisasi dan penyuluhan kepada masyarakat, pemuda dan mahasiswa tentang seputar pemilihan umum, legislatif harus lebih aktif, pencerdasan mengenai hoax dan menolak penyebaran isu yang tidak sehat. Kata kunci : Isu SARA, Pilpres, Sikap Mahasiswa.